Çiftliks, Landed Elites, and Tax Allocation in Eighteenth-Century Ottoman Veroia - Yannis Spyropoulos; Stefanos Poulios; Antonis Anastasopoulos (European Journal of Turkish Studies, 2020)
This article examines the spread of landed estates (çiftliks) in the rural areas of the Balkan district (kaza) of Veroia (Ott. Karaferye) in the course of the eighteenth century, and its impact on tax-allocation practices. In the light of a thorough analysis of various types of registers of apportionment (tevzi defterleri) of taxes and other communal expenses among the local population, we argue that the expansion of çiftliks held by ayan to the detriment of peasant landholdings had an important impact on tax-allocation processes, which ultimately adopted the çiftlik as the standard taxpaying unit. This development reflected a new social, political, and fiscal reality that is exemplified by the case of Sarıcazade el-Hac Mehmed Ağa and his family, which is discussed in the second part of the article. As our focus is on the interconnection between investment in landed property and involvement in the tax-allocation system, we discuss and contextualise the picture that emerges from the registers of apportionment in regard to the Sarıcazade family’s accumulation of land. In their capacities as landholders and local political actors, the Sarıcazades personify both the empowerment and fluidity of status and wealth of provincial elites in the eighteenth-century Ottoman Empire.